An Investigation of Ground Water Resources Quality in Sistan and Baluchistan Province, 2015 - Mojtaba Afsharnia (Journal of Global Pharma Technology, 2017)
Sistan and Baluchistan province with an area of 187.500 km2, accounts for 11.4% of the total area of the country as the biggest province. Considering the population density, it is one of the lowest populated provinces in Iran. Quality of the ground water is determined by its chemical, physical, and biological properties. Since chemical elements play a significant role in the type and amount of the usage of these resources, in this work, it's been aimed to determine and interpret the dominant type of water and critical points by measuring the important and influential physical and chemical properties including the concentrations of sulfate, fluoride, calcium, chloride, magnesium, and sodium ions, as well as other physical and chemical parameter in 800 samples from different areas of the province in 2015. The final goal is to contribute to solving the current water crisis of the country by gaining the knowledge for better management of these water resources, now and in the future. The results demonstrated that, in all cities of the province, all parameters were within the limited range, except for sodium, which was revealed to be higher than the limited range in majority of the cities. Among these cities, the quality of the water in Zahedan and Chabahar was obtained to be comparatively worse. Furthermore, the dominant type in Sistan and Baluchistan province was detected to be sodium sulfate and then sodium bicarbonate.Keywords: Chemical elements, water quality, ground water, GIS, Sistan and Baluchistan